LEARNING STYLE : Concept and Implication for Language Learning - Hasanah, Dewi (Reflective, 2012)
Many research and reviews in the field of language teaching have been increasingly recognizing the importance of learner factors in the success of language learning. The concerns about learners- center activities also seem to be a widespread agreement. They have the potential to to create conducive learning approach and opportunities for themselves. One of the learnersâ inner factors is learning styles as a natural, habitual, preferred ways of absorbing, processing, and retaining new information and skills. The styles are as a preferred mode, ones in which a learner is more comfortable learning and at last it is expected to gain language learning objectives.